Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Thay x =\(3-\sqrt{5}\) ta có:
\(A=3-\sqrt{5}-2-\sqrt{3-\sqrt{5}}\)
\(A=1-\sqrt{5}-\sqrt{3-\sqrt{5}}\)
\(\sqrt{2}A=\sqrt{2}\left(1-\sqrt{5}\right)+\sqrt{5}-1\)
\(\sqrt{2}A=\left(1-\sqrt{5}\right)\left(\sqrt{2}-1\right)\)
\(A=\frac{\left(1-\sqrt{5}\right)\left(\sqrt{2}-1\right)}{\sqrt{2}}\)
a, Với \(x>0;x\ne1\)
\(P=\left(\frac{\sqrt{x}}{2}-\frac{1}{2\sqrt{x}}\right)^2\left(\frac{\sqrt{x}-1}{\sqrt{x}+1}-\frac{\sqrt{x}+1}{\sqrt{x}-1}\right)\)
\(=\left(\frac{x-1}{2\sqrt{x}}\right)^2\left(\frac{x-2\sqrt{x}+1-x-2\sqrt{x}-1}{x-1}\right)\)
\(=\frac{x^2-2x+1}{4x}.\frac{-4\sqrt{x}}{x-1}=\frac{1-x}{\sqrt{x}}\)
Thay x = 4 => \(\sqrt{x}=2\)vào P ta được :
\(\frac{1-4}{2}=-\frac{3}{2}\)
c, Ta có : \(P< 0\Rightarrow\frac{1-x}{\sqrt{x}}< 0\Rightarrow1-x< 0\)vì \(\sqrt{x}>0\)
\(\Rightarrow-x< -1\Leftrightarrow x>1\)
\(x=3-\sqrt{5}=\frac{1}{2}.\left(6-2\sqrt{5}\right)\)\(=\frac{1}{2}.\left(\sqrt{5}-1\right)^2\)
\(\Rightarrow x>0\)\(\Rightarrow\sqrt{x}=\sqrt{\frac{1}{2}.\left(\sqrt{5}-1\right)^2}\)\(=\frac{\left|\sqrt{5}-1\right|}{\sqrt{2}}=\frac{\sqrt{2}\left(\sqrt{5}-1\right)}{2}\)\(=\frac{\sqrt{10}-\sqrt{2}}{2}\)
Thay \(x=3-\sqrt{5};\sqrt{x}=\frac{\sqrt{10}-\sqrt{2}}{2}\)vào A ta được:
\(A=3-\sqrt{5}-2-\frac{\sqrt{10}-\sqrt{2}}{2}\)\(=\frac{6-2\sqrt{5}-4-\sqrt{10}+\sqrt{2}}{2}\)\(=\frac{2+\sqrt{2}-\sqrt{10}+2\sqrt{5}}{2}\)